1969
DOI: 10.1049/piee.1969.0250
|View full text |Cite
|
Sign up to set email alerts
|

Rating of bare overhead conductors for intermittent and cyclic currents

Abstract: Equations are derived and solutions given for determining the variation with time of the temperature of bare overhead conductors carrying intermittent and cyclic currents. The temperature variation depends on the rate of heat input, the heat capacity of the conductor and the rate of total heat transfer. The latter is proportional to (temperature rise) 9 . If the heat transfer by radiation can be neglected, q = 1 for forced convection and approximately 1 • 25 for natural convection. If radiation is not negligib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Finally, an analytical approach obtained by V.T. Morgan from the general heat equation for a homogeneous and isotropic solid can be utilized [4,9]. This leads to a time response function for each variable which depends on the thermal time constant of the conductor (Fig.…”
mentioning
confidence: 99%
“…Finally, an analytical approach obtained by V.T. Morgan from the general heat equation for a homogeneous and isotropic solid can be utilized [4,9]. This leads to a time response function for each variable which depends on the thermal time constant of the conductor (Fig.…”
mentioning
confidence: 99%
“…In 1958, House and Tuttle at Alcoa Research Laboratories (USA) suggested the steady state ampacity model [11], which is basically the one currently used. About ten years later, Morgan [12] at the National Standards Laboratory of Sydney (AU) proposed a similar steadystate rating model, while [13,14] at Jersey Central Power (USA) proposed dynamic models for describing the thermal behaviour of conductors. These models are the basis of the International Council for Large Electric Systems (CIGRE) [1] and Institute of Electrical and Electronics Engineers (IEEE) [15] models still broadly used today.…”
Section: Historical and Practical Perspectivesmentioning
confidence: 99%
“…Many experimental studies [4][5][6][7][8][9][10][11][12] have shown that the radial temperature of conductors is not evenly distributed. IEEE specifications [13] proposed that there is radial temperature gradient among each layer.…”
Section: Introductionmentioning
confidence: 99%